A Radiologist's Self-Dissection and Therapy. Issue 4 (2nd October 2021) - Wu, Tayu; Yi-Jui Wu, Harry
Abstract: In this interview, the physician artist, Tayu Wu, reflects on his career trajectory and the story behind the painting selected as the journal cover. He reveals how his continuing interest in visual studies has an impact on his practice as a radiologist. He also explains the motivation behind the painting series, Bable 101, regarding the relationship between art creation and therapy. Lastly, through his own interdisciplinary practice, Wu describes the Inseparability between art and medical practice.